2000
DOI: 10.1345/aph.19116
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Antidiuretic Hormone Secretion Associated with Lisinopril

Abstract: SIADH should be considered a rare, but possible, complication of therapy with lisinopril and other ACE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
9
0
7
Order By: Relevance
“…Increasing circulating angiotensin I enters the brain and is converted to angiotensin II, which may stimulate thirst and the release of antidiuretic hormone from the hypothalamus, eventually leading to hyponatremia. 10 Mahon et al 18 demonstrated a 5-fold increase in plasma antidiuretic hormone concentrations after intracerebroventricular injection of angiotensin II in the forebrain of Lister hooded rats. Indeed, in rats, a dose-dependent effect of captopril on water intake has been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing circulating angiotensin I enters the brain and is converted to angiotensin II, which may stimulate thirst and the release of antidiuretic hormone from the hypothalamus, eventually leading to hyponatremia. 10 Mahon et al 18 demonstrated a 5-fold increase in plasma antidiuretic hormone concentrations after intracerebroventricular injection of angiotensin II in the forebrain of Lister hooded rats. Indeed, in rats, a dose-dependent effect of captopril on water intake has been described.…”
Section: Discussionmentioning
confidence: 99%
“…For the following reasons, we considered hyponatremia in our patient as an adverse drug reaction associated with ACE inhibitors. ACE inhibitors-including captopril, lisinopril, and enalapril-have been reported previously as a cause of severe hyponatremia [4][5][6][7][8][9][10][11] (Table Serum sodium I). Seventeen cases of severe hyponatremia induced by ACE inhibitor therapy have been reported in the literature-5 with captopril, 3 with lisinopril, and 9 with enalapril, including our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is the preservation of bradykinin's (endothelium-dependent, nitric oxideand prostacyclin-mediated) vasodilator effect that is thought to lend added salutary value to ACE inhibition. Still other adverse reactions, such as syndrome of inappropriate ADH secretion, although appearing to still be ACE inhibitor classdependent, are more esoteric, although enhanced brain angiotensin levels arising from hyper-reninaemia have been suggested to play a role [25,26]. The incidence of taste disturbance seems to be restricted to the use of sulfhydryl-containing agents such as captopril and is easily avoided by selecting an alternative chemical class of ACE inhibitor.…”
Section: Acementioning
confidence: 99%
“…Diese in der Klinik häufig eingesetzten Medikamente hemmen die periphere -nicht die zentrale -Konversion von Angiotensin I in Angiotensin II. Das peripher ansteigende Angiotensin I kann zentral in Angiotensin II umgewandelt werden, welches das Durstzentrum und die ADH-Freisetzung stimuliert [30].…”
Section: Syndrom Der Inappropriaten Adh-sekretionunclassified